2017
DOI: 10.1136/bjsports-2016-096422
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and other non-pharmaceutical interventions for cancer-related fatigue in patients during or after cancer treatment: a systematic review incorporating an indirect-comparisons meta-analysis

Abstract: AimTo assess the relative effects of different types of exercise and other non-pharmaceutical interventions on cancer-related fatigue (CRF) in patients during and after cancer treatment.DesignSystematic review and indirect-comparisons meta-analysis.Data sourcesArticles were searched in PubMed, Cochrane CENTRAL and published meta-analyses.Eligibility criteria for selecting studiesRandomised studies published up to January 2017 evaluating different types of exercise or other non-pharmaceutical interventions to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
208
3
20

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 289 publications
(235 citation statements)
references
References 64 publications
4
208
3
20
Order By: Relevance
“…In cancer survivors, an inverse correlation between PA and mortality or recurrence rate was reported . Moreover, EX can play a beneficial role during and after oncological treatments, leading to clinically meaningful improvements in physical fitness (aerobic, strength, flexibility, and body composition) , quality of life (QoL) , treatment‐related side effects , and psychological outcomes (such as anxiety, depression, self‐esteem, and energy level and vitality) . Nevertheless, the American College of Sport Medicine guidelines for EX in cancer are mainly directed to patients with breast, prostate, colon, gynecologic, and hematological cancer, and no universal recommendations are available for lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer survivors, an inverse correlation between PA and mortality or recurrence rate was reported . Moreover, EX can play a beneficial role during and after oncological treatments, leading to clinically meaningful improvements in physical fitness (aerobic, strength, flexibility, and body composition) , quality of life (QoL) , treatment‐related side effects , and psychological outcomes (such as anxiety, depression, self‐esteem, and energy level and vitality) . Nevertheless, the American College of Sport Medicine guidelines for EX in cancer are mainly directed to patients with breast, prostate, colon, gynecologic, and hematological cancer, and no universal recommendations are available for lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interventions including physical activity and psychological and pharmacologic approaches have been investigated for the management of fatigue in cancer patients, and several systematic reviews have been published [14][15][16][17][18][19][20][21][22] . The evaluation of pharmacologic interventions is particularly important, because medications can be associated with adverse effects and high costs.…”
Section: Introductionmentioning
confidence: 99%
“…A Cochrane Review found that methylphenidate was the only agent that caused a significant, albeit small, improvement in CRF . There are a growing number of studies investigating nonpharmacologic treatments for CRF; for example, data suggest that exercise causes a small to moderate decrease in CRF . The psychosocial interventions studied have reported small but significant reductions in fatigue .…”
Section: Introductionmentioning
confidence: 99%
“…13 There are a growing number of studies investigating nonpharmacologic treatments for CRF; for example, data suggest that exercise causes a small to moderate decrease in CRF. [14][15][16][17][18][19] The psychosocial interventions studied have reported small but significant reductions in fatigue. 14,20,21 Overall, methodology and design challenges continue to limit the impact of this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation